2014
DOI: 10.4103/1319-3767.133003
|View full text |Cite
|
Sign up to set email alerts
|

Egy-score as a noninvasive score for the assessment of hepatic fibrosis in chronic hepatitis C: A preliminary approach

Abstract: Background and Aims:Egy-Score is a new noninvasive score for prediction of severe hepatic fibrosis in patients with chronic liver diseases. The aim of this study was to validate Egy-Score as a noninvasive score for predicting stage of hepatic fibrosis in a group of Egyptian chronic hepatitis C patients.Patients and Methods:One hundred Egyptian patients with chronic hepatitis C were enrolled. Mean age was 40.25 ± 9.39 years. They were subjected to CA19-9, alpha-2-macroglobulin, total bilirubin, platelet count a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…In the current study Egy‐score was able to diagnosis significant fibrosis (≥F2) at cutoff value ≥4.73 with 63% sensitivity and 67% specificity. Moreover our results showed less sensitivity and specificity in the detection of significant hepatic fibrosis (≥F2) than the original validation study of the Egy‐score that showed sensitivity of 75.8% and specificity of 68.42% at cut off 2.9 …”
Section: Discussioncontrasting
confidence: 87%
“…In the current study Egy‐score was able to diagnosis significant fibrosis (≥F2) at cutoff value ≥4.73 with 63% sensitivity and 67% specificity. Moreover our results showed less sensitivity and specificity in the detection of significant hepatic fibrosis (≥F2) than the original validation study of the Egy‐score that showed sensitivity of 75.8% and specificity of 68.42% at cut off 2.9 …”
Section: Discussioncontrasting
confidence: 87%
“…"Egy-Score" has been developed for the noninvasive assessment of hepatic fibrosis and cirrhosis. Egy-Score has shown good sensitivity, specificity, PPVs and NPVs, and AUROCs for predicting significant fibrosis (≥ F2), severe hepatic fibrosis (≥ F3), and cirrhosis (F4) [15]. Liver stiffness measurement (LSM) can be used to assess liver fibrosis in patients with CH.…”
Section: Discussionmentioning
confidence: 99%